Successful percutaneous coronary intervention of left main coronary artery dissection following mechanical aortic valve replacement surgery: a case report and literature review - Vu, Vu Hoang; Truong, Hung Phi; Tran, Hoa; Cao, Khang Dang; Duong, Bao Thien; Tran, Thuy Thanh Thi; Truong, Binh Quang (Frontiers in Cardiovascular Medicine, 2024)
Background Iatrogenic left main coronary artery (LMCA) dissection resulting from cardiac surgery is a rare complication. Its early detection is challenging and often poses a significant threat to the patient's life. However, evidence regarding the most effective management strategy for this condition remains limited at present. Case presentation We present a case of 65-year-old female patient who developed cardiogenic shock after mechanical aortic valve replacement surgery associated acute myocardial infraction. Despite concurrent coronary artery bypass graft (CABG) surgery, the patient's condition remained unimproved. Subsequent coronary angiography revealed extensive LMCA dissection involving the left circumflex (LCx) artery. Percutaneous coronary intervention (PCI) guided by intravascular ultrasound (IVUS) led to an immediate improvement in hemodynamic status. The patient was successfully discharged after 22 days of treatment. Conclusions Iatrogenic LMCA dissection is an uncommon complication following cardiac surgery. It can manifest in a variety of ways, including as incidental findings, cardiogenic shock or sudden cardiac arrest. The precise prevalence rates of causes linked to cardiac surgery remain largely unknown due to the scarcity of reported cases and the absence of research on this issue. Currently, a definitive management strategy for this condition has not been established. However, previous reported clinical cases provide insight that CABG could be considered if coronary artery dissection is detected during cardiac surgery. Upon postoperative identification, diagnostic coronary angiography and PCI may be feasible alternatives.